Combined versus single treatment regimens for keloid therapy using serial intralesional corticosteroid injections, surgical excision, silicone- and/or cryotherapy. (September 2021) - Jacobs, C.; Wilmink, J.
Abstract : Efficacy comparison of several regimens in treating keloids as combined or standalone therapies could provide essential information for selecting appropriate therapy. This study retrospectively evaluated the treatment efficacy of corticosteroid injections, excision, silicone, cryotherapy, or combinations of these for treating keloids. Additionally, the use of corticosteroid injection schemes and combined cryotherapy regimens were analysed. Retrospective chart analysis was performed on 204 keloids treated patients at the plastic surgery department of the Máxima Medical Centre between 2009 and 2018. The patient's age, gender, treatment, anatomic location, scar aetiology, previous therapy, scar recurrence, additional therapy, and follow-up duration were retrieved. Treatment efficacy was assessed through treatment failure, defined by the recurrence or lack of response. Kaplan–Meier and Cox survival analyses were performed to compare treatment efficacy between the different regimens. Monotherapies exhibited a significantly higher chance of treatment failure (HR 2.4, 95% CI 1.4–4.2, p<0.05) when compared to combined therapies. Sporadic corticosteroid injections demonstrated more treatment failure overall (HR 3.5 95% CI 1, 6–7, 3; p=0.001), but did not differ significantly from injection schemes. Combined cryotherapy efficacy did not differ significantly from the other combined regimens (HR 1, 6 95% CI 0, 5–5, 1; p=0.401). Combined therapies exhibited clear superiority over monotherapies. Sporadic corticosteroid injections demonstrated inferior results compared to all other therapies. Combined cryotherapy cases were insufficient, and more data are required for proper assessment. Future prospective assessments of corticosteroid injection schemes and combined regimens are warranted.